In-house design of forced convection direct chill casting simulator for casting immiscible Al-Sn alloys. (2nd November 2021) - Patel, Deepak; Kundu, Amrik; Kundu, Arjun; Biswas, Prasenjit; Kotadia, Hiren R.; Mallik, Archana; Das, Sanjeev
ABSTRACT: Al-Sn immiscible alloys possess enhanced tribological properties with increased fatigue strength, which makes them competent among self-lubricating bearing materials. In the present work, a direct chill (DC) casting simulator has been designed and manufactured to cast Al-Sn alloy by forced convection technology. The study embodies two different mechanisms for mechanical forced convection (MFC) by: (i) high shear (HS) rotor-stator device, (ii) conventional stirrer (CS) without stator. Shearing rate of 800 rpm for 60 seconds were kept constant for both the cases. Severe segregation of Sn has been observed in CS-DC cast billet due to prevailed phase separation and gravity sedimentation of Sn-rich phase from Al matrix. However, in the case of HS-DC cast billet uniform distribution of Sn and fine equiaxed grains throughout the volume of the billet has been achieved.